Mental Health and Job-Satisfaction among Government and Private Hospital Doctors - Praveen Kumar. K.B (CV. Doki Course and Training, 2026)
In the present study was conducted to examine the mental health and job satisfaction among government and private hospital doctors. The human life changed regularly many causes are influenced on that changes so this condition effects on human health especially human mental health. Mental health includes our feelings, emotions, thoughts, psychological, social well-being and sexual well-being and human job satisfaction also is more essential to lead life in future. A random sample of 30 doctors from various hospitals from the districts of Shivamogga and Chikamangalore (15 from government hospitals and 15 from private hospitals). Age range between 30-50 years. For the objective of these study two psychological tests is used to measures. Mental health inventory developed by Dr. Jagdish and Dr. A.K. Srivastava (1983) and job satisfaction scale developed by Dr. Amar Singh and T.R. Sharma (1999) was used to measure job satisfaction. The obtained data was analysed by using mean, SD and‘t’- test was applied. Further, Spearman’s coefficient of correlation was applied. The result of the study concluded that there is no significant difference between government and private hospital doctors on mental health and there is a significant difference between government and private hospital doctors on job satisfaction and also there is a significant relationship between mental health and job satisfaction among government and private hospital doctors.